Efficient Surgical Cutting with Position-Based Dynamics - Berndt, Iago; Torchelsen, Rafael; Maciel, Anderson (IEEE computer graphics and applications, 2017)
This paper addresses common problems with traditional surgery simulation scenarios and proposes PBD-based solutions. Specifically, it introduces a skinning scheme that supports interactive tissue cutting with haptic feedback. In addition, it also presents a method to configure cluster constraints with PBD and an approach to simulate electrosurgery.